Zinc Oxide and Aloe Vera Gel Therapy Wound Care on Healing Diabetic Ulcers - Tarkawi; Saputra, Rangga; Rusmiayunita, Siti; Agustin, Siti Sarah; Diana, Sri; Nurfalyya, Tia (INDOGENIUS, 2025)
Background & Objective: Diabetic ulcers are a chronic complication of diabetes mellitus that are difficult to heal and carry a high risk of amputation. Wound healing in people with diabetes is often hampered by impaired circulation, neuropathy, and infection. Topical therapies such as zinc oxide cream And Aloe Vera gel They have been used to accelerate healing through different but complementary mechanisms. To determine the effectiveness of topical zinc oxide cream and aloe vera gel on the healing of diabetic ulcers based on recent research results. Method: Using the literature review method by searching for articles in the PubMed, ScienceDirect, Google Scholar databases, Connected Papers, Research Gate and Research Square, with publications spanning 2015–2025. Of the 25 articles found, 7 met the inclusion criteria. Result: Aloe Vera gel has been shown to be effective in accelerating the healing of diabetic ulcers by reducing wound assessment scores (Bates-Jensen, Winner Scale), increasing tissue regeneration, and shortening the inflammatory phase. Zinc Oxide cream has been shown to accelerate the transition from the inflammatory phase to the proliferative phase, protect wound tissue from bacterial colonization, and support collagen synthesis. Several preclinical studies combining Aloe Vera with Zinc Oxide nanoparticles have shown accelerated wound closure compared to single treatments. No serious side effects were found from the use of these two therapies. Conclusion: Zinc oxide cream and aloe vera gel are both effective in accelerating the healing of diabetic ulcers through complementary mechanisms. Both are safe, accessible, and affordable, making them potentially useful adjuvant therapies in healthcare settings. Further research, including controlled clinical trials of a pure combination of the two therapies, is needed to confirm their effectiveness and safety.